The Uterotonic Screening of the Root Extract of Azanza garckeana (Malvaceae) on Isolated Wistar Rat Uterine Smooth Muscles. (9th December 2020) - Chanda, Alfred; Simwinga, Freddie; Kaonga, Patrick; Gono-Bwalya, Angela; Prashar, Lavina
Abstract : Introduction . Azanza garckeana (F.Hoffm.) Exell and Hillc. (family: Malvalceae) is traditionally used to induce or accelerate labour in pregnant women in Chongwe, Zambia, and the plant part which is commonly used are the roots. Aim . The aim of this study was to screen Azanza garckeana crude extracts for uterotonic activity on isolated Wistar rat uterine smooth muscles. The likely mechanism of action for the plant extract was also investigated. Materials and Methods . Fresh leaves and roots of the plant were collected and identified by a botanist at the University of Zambia. The methanol and cold root aqueous extracts were prepared by continuous maceration while the hot aqueous root extract was extracted using the Soxhlet method. The crude extracts of the plant were screened for uterotonic activity using uterine smooth muscles isolated from estrogenised adult nongravid female Wistar rats weighing between 160 g and 200 g. The activity of the plant was also evaluated in the presence of antagonists and tocolytic agents to determine the likely mechanism of action. Results . The hot aqueous root crude extract (22.26%) had the highest yield followed by the cold aqueous (11.32%) and methanol extracts (6.26%), respectively. The methanol crude root extract demonstrated the highest potency (EC50  = 1.28 × 10 −2  mg/ml; 95% CI 6.418 × 10 −3 to 2.564 × 10 −2 ; p = 0.0001 ), while the cold aqueous extract was the most efficacious. Salbutamol and nifedipine significantly blocked the uterotonic activity of the extract. Conclusions . This study provides scientific evidence on the uterotonic activity of Azanza garckeana with myometrial calcium mobilization as the possible mechanism of action.